2007
DOI: 10.1248/jhs.53.220
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Single Treatment with Keishininjinto on Plasma Levels of Gut-regulatory Peptides in Healthy Subjects

Abstract: A traditional Japanese Kampo medicine Keishininjinto has been empirically used for the treatment of headache, chronic gastroenteritis, gastric atony, and waterly diarrhea often accompanying abdominal pain, cold, fever, and headache. One of the mechanisms of the empirical effects is assumed to be due to local changes in gut-regulated peptide levels. We studied the effects of Keishininjinto on calcitonin gene-related peptide (CGRP)-, substance P-, vasoactive intestinal polypeptides (VIP)-, motilin-, and somatost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…7) It is know that this herb or some Kampo medicines which include this herb increased plasma CGRP-IS levels in human subjects. 11,24,25) Accordingly, Bushi-richu-to may also directly stimulate CGRP-containing nerves or indirectly secrete CGRP accompanied by the stimulation of other secretory cells and mechanisms. The mechanisms of Bushi-richu-to, based on the increment of CGRP-IS levels in human plasma, might include not only the improvement of peristaltic contractions but also increments in intestinal blood flow, both of which are mediated by CGRP.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…7) It is know that this herb or some Kampo medicines which include this herb increased plasma CGRP-IS levels in human subjects. 11,24,25) Accordingly, Bushi-richu-to may also directly stimulate CGRP-containing nerves or indirectly secrete CGRP accompanied by the stimulation of other secretory cells and mechanisms. The mechanisms of Bushi-richu-to, based on the increment of CGRP-IS levels in human plasma, might include not only the improvement of peristaltic contractions but also increments in intestinal blood flow, both of which are mediated by CGRP.…”
Section: Resultsmentioning
confidence: 99%
“…Dai-kenchuto, Ninjin-to and Keishi-ninjin-to affect gastrointestinal motility and based on empirical evidence their effects are assumed to be an alteration of gut-regulated peptides levels in healthy human plasma. [9][10][11] Among these drugs, it is reported that Ninjin-to potentially enhances gastrointestinal motility in a manner similar to that of gastrointestinal prokinetic drugs like cisapride and meto-clopramide. 12) Ninjin-to and Bushi-richu-to contain the same herbs (Ginseng radix, Glycyrrhizae radix, Atractylodis rhizome, and Zingiberis siccatum rhizome).…”
Section: Introductionmentioning
confidence: 99%